Steel slag mineral carbonation: a critical review on mechanisms, operational parameters, and valorization strategies for CO₂ sequestration - Guio, Laura Loyola Marion; Carvalho, Franciely Lorenzon; Moro, Larissa Bernardino; Nariyoshi, Yuri Nascimento; Oliveira, Jairo Pinto de; Cassini, Sérvio Tulio Alves (Brazilian Journal of Production Engineering, 2025)
The steel industry is one of the largest global contributors to carbon dioxide (CO₂) emissions, accounting for 7% to 9% of the world’s total. In this context, mineral carbonation of steel slags emerges as a promising strategy for permanent CO₂ sequestration and the valorization of industrial waste. This paper presents a critical and systematic review of the literature from 2014 to 2024, exploring fundamental mechanisms, the influence of operational parameters, and the valorization potential of carbonated steel slag. The analysis revealed that, although ladle furnace (LF) and basic oxygen furnace (BOF) slags stand out for their reactivity, sequestration efficiency varies significantly with operational conditions. Indirect methods and supercritical carbonation demonstrated high effectiveness, with capture rates that can exceed 90% and 41.9%, respectively. Pilot-scale studies corroborate feasibility, with reported efficiencies of up to 89.7%. Optimizing parameters such as temperature (around 60-90°C), liquid-to-solid ratio (L/S of 4:1), and fine particle size is crucial, although the effect of CO₂ pressure can vary and, in some cases, excessive pressure may reduce efficiency. Carbonated products have wide applications in civil construction as aggregates and binders, improving volume stability and immobilizing heavy metals, which can reduce CO₂ emissions in concrete production by up to 30%. Challenges such as slag composition variability and high energy consumption for grinding persist. It is concluded that method standardization, parameter optimization, and the promotion of industrial-scale projects are essential to maximize the potential of steel slag as a sustainable solution for decarbonization and the circular economy.